Antimicrobial potential of essential oils mouthrinses with and without alcohol - Matheus Grunevald; Rômulo Cantarelli; Harry Juan Rivera Oballe; Thais de Cássia Negrini; Rodrigo Alex Arthur; Eduardo Liberato da Silva; Tiago Luis Herpich; Francisco Wilker Mustafa Gomes Muniz (Universidade Estadual de Campinas, 2021)
Aim: This study aimed to compare the microbiological potential and gustatory perception of essential oils (EO) mouthrinses containing and not containing alcohol. Methods: Twenty healthy adult volunteers rinsed with 10mL of the following test solutions: EO with alcohol, EO without alcohol, or a control solution (saline solution with mint essence). A washout period of at least seven days was adopted after a single-use protocol of the respective solution. All participants used all three tested substances. Antimicrobial potential was assessed by counting salivary total viable bacteria both before and after each rinse. Gustatory perception was evaluated using the Visual Analogue Scale (VAS). Multiple comparisons were performed with the Wilcoxon test, using Bonferroni correction. Results: Both EO solutions presented a higher antimicrobial potential in comparison to the control solution (p<0.017). However, no significant difference in antimicrobial potential was observed between EO containing or not containing alcohol (p=0.218). VAS of EO with alcohol (median: 2.7) was similar to control solution (median: 1.6) (p=0.287). A better gustatory perception was observed of the EO without alcohol (median 7.6) when compared to the control solution (p<0.0001). When EO groups were compared, EO without alcohol also demonstrated a significantly better gustatory perception (p=0.001). Conclusion: Mouthrinse containing EO without alcohol presented a better taste perception when compared to the EO with alcohol, but no difference was observed in the antimicrobial potential of both EO solutions after a single rinse protocol.